On the Latimer-MacDuffee theorem for polynomials over finite fields - Van Zyl, Jacobus Visser (Stellenbosch : University of Stellenbosch, 2011)
Thesis (PhD (Mathematical Sciences))--University of Stellenbosch, 2011.